P357 Monitoring of Thiopurines and Methotrexate in Inflammatory Bowel Disease: Are we Monitoring Too Frequently? A Cross Sectional Study. (21st January 2022) - Liao, Y W; Oh, S; Wright, A; Evans, C; Duff, C; Farmer, A; Fryer, A
Abstract: Background: The use of immunosuppressive medications such as thiopurines and methotrexate (MET) are commonly employed in inflammatory bowel disease (IBD) to control symptoms and maintain remission. The British Society of Gastroenterology recommends three monthly full blood count (FBC) and liver function tests (LFT) to monitor for myelotoxicity and hepatotoxicity after being established on therapy. However, the quality of evidence for this is low. Due to the high burden of blood tests and patients becoming increasingly apprehensive to attend hospital or their general practice surgery in the midst of a pandemic, we aimed to investigate (1) the feasibility to adhere to these recommendations and (2) the frequency of abnormal blood test when recommendations are adhered. Methods: We performed a, 12-month cross sectional study from July, 2017 to July, 2018 of patients established on azathioprine (AZA), 6-mercaptopurine (6-MP), or MET. The timeline was split into four windows of three months each. A patient was removed from the study if they reached any one of these six end points: no FBC or LFT checked within a window, new abnormal LFT, white cell count (WCC) less than, 3.5, change in medication, change in dosage, and medication stopped. Results: As of, 2019, 4327 patients were under the care of our specialist IBD team with, 1081 on active therapy. We identified, 205 patients who were established on these agents (AZA = 156, 6-MP = 41, MET = 8) within the determined study period. A total number of, 96 patients reached an end point during this period. For our first objective, a patient was deemed to have been monitored if FBC and LFT was checked at least once during a window., 26% (54/212) of patients were removed from the study as they did not fulfil this criteria. Of the remaining, 41 patients who reached an end point, 14 were due to a new abnormal LFT result (AZA = 8, 6-MP = 6, MET = 0) and, 5 due to a WCC less than, 3.5 (AZA = 4, 6-MP = 1, MET =0). Excluding non-adherent patients, our study revealed only, 12% (19/158) of patients had to discontinue therapy due to an abnormal blood test. Conclusion: Achieving an adherence of, 74% was possible with a team of dedicated IBD specialist nurses and doctors in a tertiary centre. Whilst there is still much room for improvement, this may be difficult to replicate in smaller centres with more limited resources. Despite the small sample size, our finding of only, 12% of abnormal blood test is consistent with similar studies done by Fournier et.al in, 2010 and Chaparro et.al in, 2013. This would certainly pose the question if we can consider monitoring less frequently.